1996
DOI: 10.2337/diacare.19.7.730
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory Variation of GHb Assays in Victoria, Australia

Abstract: A substantial degree of interlaboratory variation for GHb measurement exists in Victoria, Australia. This may lead to difficulties in interpretation when GHb is assayed by different laboratories in the same patient over time. Interlaboratory standardization may be achievable by calibration to a standard assigned by a reference laboratory and distributed to all laboratories measuring GHb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…No entanto, os valores de GHb/HbA 1c fornecidos por um laboratório podem não corresponder com os valores fornecidos por outro laboratório, mesmo usando o mesmo método e medindo a mesma fração. Não existe concordância entre os valores de referência e a comparação dos resultados é muito difícil (5,35,(47)(48)(49). A mesma amostra pode apresentar um valor de 7% em um laboratório e 9% em outro.…”
Section: Padronização E Harmonização Dos Resultadosunclassified
“…No entanto, os valores de GHb/HbA 1c fornecidos por um laboratório podem não corresponder com os valores fornecidos por outro laboratório, mesmo usando o mesmo método e medindo a mesma fração. Não existe concordância entre os valores de referência e a comparação dos resultados é muito difícil (5,35,(47)(48)(49). A mesma amostra pode apresentar um valor de 7% em um laboratório e 9% em outro.…”
Section: Padronização E Harmonização Dos Resultadosunclassified
“…HbA1c analysis results are subject to variation as a result of the type of equipment used, with the analysis method accounting for differences of up to 23% in the result [36,37]. In the course of this study, changes in the equipment and methods used for HbA1c analysis were monitored via communication with the two pathology companies to assess the need for sensitivity analyses exploring the size of any such effect.…”
Section: Discussionmentioning
confidence: 99%
“…The issues with the technical aspects of the assay were highlighted by studies in which samples for the measurement of HbA 1c were split between assays, yielding extreme variability in the results (35,36). Indeed, large epidemiological studies have suggested that HbA 1c testing is less sensitive than FPG measurement in terms of its diagnostic capabilities (37,38).…”
Section: Conclusion -Previous Reportsmentioning
confidence: 99%